2018
DOI: 10.11648/j.rs.20180302.13
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiology of Sport Injury Rates Among Campus Recreation Sport Programs

Abstract: Injuries are one of the common risks associated with physical activity. At the collegiate level of sports participation, NCAA sports programs are required to provide injury treatment and prevention options for their athletes. However, for participants competing in club and intramural sports, no universal requirements for injury prevention and treatment exist. This study assessed the risk of injury during club and intramural sports among college-aged students compared to participants in NCAA sports. Overall, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…The average injury rate (per 1000 playing and training hours) found in the present study was 2.64 per 1000 h. This figure is considerably lower than the rate observed by Arthur-Banning et al [ 31 ] in practices in NCAA and club sports among college athletes, which was respectively 3.9 and 3.8. However, in the same study, they reported an injury rate during game competitions of 18.3 in club sports, 13.79 in NCAA, and 10.28 in intramural sports.…”
Section: Discussioncontrasting
confidence: 75%
“…The average injury rate (per 1000 playing and training hours) found in the present study was 2.64 per 1000 h. This figure is considerably lower than the rate observed by Arthur-Banning et al [ 31 ] in practices in NCAA and club sports among college athletes, which was respectively 3.9 and 3.8. However, in the same study, they reported an injury rate during game competitions of 18.3 in club sports, 13.79 in NCAA, and 10.28 in intramural sports.…”
Section: Discussioncontrasting
confidence: 75%
“…erefore, how to prevent and control the risk of college sports have become key issues to be solved urgently. Strengthening and improving the research for risk assessment for college sports is not only a theoretical hotspot, but also an urgent practical task [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The limited involvement by universities indicates that club sport athletes do not receive the same injury prevention education as varsity sports and that responsibility falls on sport club officers. While the National Intramural-Recreational Sports Association (NIRSA) does not currently have an injury reporting system, a previous study by Arthur-Banning et al (2018) found that club sports have a significantly higher rate of injury compared to previouslydocumented NCAA athletes. With a high injury rate and no national organization mandating specific concussion protocols or guidelines, there is a need to explore current practices in club sports concussion education and knowledge to understand the factors associated with SRC underreporting in club athletes (Musille, 2016).…”
Section: Collegiate Sports Vs Club Sportsmentioning
confidence: 99%